(untitled) (Teología, 2015)
In this lecture, written for the Conference in the Centenary of the Faculty of Theology of the Catholic University of Argentina, the author, beginning with his own memories, analyzes the historical context of great transformations in which the Council took place, and the triumph of the idea of renovation, inspired in the sources of the life of the Church and reflected in the conciliar documents. The reception of these results in the post-Council proved to be a difficult process: in Latin America, due to the debates related to the Theology of Liberation; in Europe, due to the challenge of modernity, Marxism and liberal individualism. During the ‘80s many debates on the interpretation of the Council arose, and strong tendencies appeared aimed at neutralizing its implementation. Pope Francis is currently facing this challenge, calling the Church to a way of evangelical radicalism, centered on mercy and the preferential option for the poor.